Chemotaxonomic Standardization of Herbal Drugs Milk Thistle and Globe Thistle - Ahmad, Mushtaq; Ajab Khan, Mir; Hasan, Aurangzeb; Zafar, Muhammad; Sultana, Shazia (Asian Journal of Chemistry, 2010)
Chemotaxonomic standardization is critically important to the quality, safety and efficacy of herbal drugs throughout the world and particularly in Pakistan where 80 % population rely on folk medicine for primary health care. In present account an attempt was made to authentify herbal drugs Silybum marianum (Milk thistle) and Echinops echinatus (Globe thistle) by using multidimensional identification techniques. Milk thistle and globe thistle have been confused with each other due to folk nomenclature problem which probably existed due to their capitulum resemblance of same tribe Cardueae of family Asteraceae. In this paper the taxonomic evidences for authentication were based on detailed studies of morphology scanning electron microscopy of pollen and leaf epidermal characteristics where as chemical standards were thin layer chromatography, ultraviolet and infrared analysis. In Silybum marianum, flavonoid agylocone revealed the presence of one major and two minor amounts of phenolic acid and Echinops echinatus can be distinguished due to the presence of three phenolic acid of small amount, when viewed under 366 nm UV light. It is concluded that these techniques have been used to authenticate problematic herbal drugs in order to maintain WHO standards for globalization of alternative system of medicine.